MORPHOGENIC STUDIES ON ANNONA RETICULATA (L.) - ARFA ANJUM; RAMESH KUMAR PANDEY (The Bioscan, 2011)
Different concentration of phytohormones affected formation of callus of Annona reticulata. Leaf of Annona reticulata was cultured on “murashige and skoog’s” (MS) medium supplemented with different concentrations of IAA, IBA, 2,4-D, NAA, KN, BAP, Coconut - water in isolation or in combination. Then white Callus was observed. Cytokinins was also used alone or in combination for callus induction. Most suitable medium for induction of Callus was 2, 4-D.